APLIKASI ALAT BANTU ERGONOMIS PADA KERJA MANUAL BERDASARKAN KAJIAN ERGO-MECHANICAL UNTUK PETANI KECIL - I Gede Bawa Susana; I Ketut Perdana Putra; I G.A.K.C. Adhi (Energy, Materials and Product Design, 2024)
Using traditional tools and manual work by small farmers in rural and developing areas is routine in processing agricultural land, especially planting plant seeds. This working model includes moderate to severe workload due to additional workload, namely sunlight when planting. In addition, work is carried out with non-ergonomic work postures, namely non-natural work postures. This causes musculoskeletal complaints to workers due to the non-harmonious tools with workers. Workers' productivity will decrease and have the potential to reduce the quality of life of small farmers themselves. To help the manual work of small farmers to create effective, comfortable, safe, healthy, efficient, and sustainable jobs, an ergo-mechanical application is needed to design work tools. This application is based on studies conducted on the design of work tools from several libraries or research results. The ergo-mechanical study is an integrated system that applies ergonomic and mechanical principles. The ergo-mechanical application produces ergonomic work tools that are comfortable to use by workers, and technical standards include material, product, and service requirements. Mechanically, the application through technical drawings, mechanical planning, and work tool materials to get a strong, lightweight, and safe work tool from hazardous substances, according to technical specifications. Technical standards are related to data sheets or specifications that describe the technical characteristics of a work tool. On the specifications of the work tool design, specifications can be added that the work tools are ergonomic. Ergonomic work tools can produce effective, comfortable, safe, healthy, and efficient work. This results from the compatibility between work tools and workers or the harmonious work tools with workers. Ergo-mechanical creates comfort in work that affects the increase in productivity and quality of life for workers.